PERANCANGAN SISTEM PAKAR MENDIAGNOSA PENYAKIT KULIT PADA ANAK DENGAN MENGGUNAKAN METODE BACKWARD CHAINING - Maiyendra, Nico Alvio (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2018)
Expert systems (expert systems) in general is trying to adopt a system of human knowledge into a computer, so the computer can resolve the problem as was done by the experts. Or in other words, the expert system is a system designed and implemented with the help of a specific programming language to be able to resolve the problem as done by experts.In this case I tried to implement an expert system to diagnose skin diseases for children from the symptoms and the causes of skin diseases for children. The purpose of this paper is to build a knowledge-based system on brain cancer using backward chaining method that will be displayed in the form of a website using PHP programming and MySQL database.